Intrahepatic biliary cystadenoma—diagnosis and treatment options - Treska, Vladislav; Ferda, Jiri; Daum, Ondrej; Liska, Vaclav; Skalicky, Tomas; Bruha, Jan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Liver cystadenomas are rare conditions accounting to approximately 5% of all cystic lesions. The aim of our study was to establish a new diagnostic and complex therapeutic approach. Materials and Methods: In all, 12 female patients primarily diagnosed with cystadenoma of the liver were evaluated. Enucleation of the cystadenoma was performed in six (54.5%) and liver resection in four (33.3%) patients. Due to the localization, complete enucleation or radical liver resection could not be performed in two patients. Results: In three patients, grade III-a complications were recorded after surgery. The 30-day mortality was 0%. The length of hospitalization was 27 (7–52) days. Malignant transformation occurred in two patients with incomplete removal of the cystadenoma. In both cases, carbohydrate antigen 19-9 serum levels were elevated during the follow-up period. The first patient died 28 months after primary surgery. The second patient failed to attend any further appointments. The remaining patients are in the good conditions, with no signs of recurrence. Conclusion: The only possible treatment of cystadenomas is their radical surgical removal. Any other incomplete surgical treatment is insufficient and associated with a high risk of malignant transformation. For patients in whom R0 resection or complete enucleation cannot be performed for technical reasons, liver transplantation should be considered.